Perbedaan Tingkat Kecukupan Vitamin A, Zat Besi, dan Zink pada Balita Stunting dan Non Stunting di Kabupaten Banyuasin - Silaban, Titin Dewi Sartika; Rahmadhani, Sendy Pratiwi; Sugiman, Turiyani (Faculty of Medicine, Universitas Andalas, 2022)
Stunting is a chronic nutritional problem in toddlers of a shorter height than children his age. The impact of stunting is not only in terms of health but also affects the level of intelligence of children. Toddlers who lack vitamin A, iron, and zinc can cause cognitive and physical impairment and an increased risk of death. Objectives: To determined the difference in the level of adequacy of vitamin A, the level of adequacy of iron and the level of adequacy of zinc in stunting and non-stunted toddlers. Methods: The research was an observational analytic with a cross-sectional design. The sample of this study was 98 toddlers aged 13-23 months in Banyuasin Regency in 2021, collected by simple random sampling technique. The data were collected by using microtoise and food recall 24h (not in arrow). Results: There was a different level of vitamin A adequacy (p-value = 0.002), the level of iron adequacy (p-value = 0.012), and the level of zinc adequacy (p-value = 0.030) Â between stunted and not stunted toddlers. Conclusion: There are differences in the level of adequacy of vitamin A, iron, and zinc between stunted and non-stunted in toddlers.Keywords: stunting, vitamin A, iron, zinc